Correlation of Urine Albumin Creatinine Ratio And C-Reactive Protein Levels on Carotid Artery Intima-Media Thickness And Flow-Mediated Dilatation Response In Children and Adolescent with Type 1 Diabetes Mellitus At Dr Saiful Anwar Hospital Malang - Seprian Widasmara; Novi Kurnianingsih; Indra Prasetya; Cholid Tri Tjahjono; Budi Satrijo (Heart Science Journal, 2022)
Background:Early and accelerated atherosclerosis is a major cause of cardiovascular disease and often causes premature death in T1DM patients. In DMT1, atherosclerosis can be detected since adolescence. The initial association between urinary albumin to creatinine ratio (ACR) and c-reactive protein (hs-CRP) with subclinical cardiovascular disease in children and adolescents with T1DM supported findings from previous studies. Imaging tests using ultrasound can detect subclinical atherosclerosis in this patient population. Carotid artery intima-media thickness (cIMT) and flow-mediated dilatation response (FMD) have been frequently used to detect subclinical atherosclerosis.Objective: To find correlation between ACR and hsCRP on the thickness values of cIMT and FMD in children and adolescent DMT1 patients at Dr Saiful Anwar Hospital MalangMethods: This is a cross-sectional study with 82 subjects of DMT1 patients who routinely control the pediatric outpatient clinic of RSUD Dr. Saiful Anwar Malang, with the research period January – July 2019 and December 2021 – March 2022.Results: There was correlation between ACR with FMD and cIMT (r=-0.593; p=0.000 and r=0.339; p=0.002, respectively). There was also correlation between hsCRP with FMD and cIMT (p=-0.375; p=0.001 and r= 0.414; p=0.023, respectively).Conclusion: ACR and hsCRP have a correlation with increasing CIMT values and decreasing FMD values in children and adolescents with DMT1 patients.